KEBERADAAN TARI KUDA LUMPING PAGUYUBAN TURONGGO MUDODI NAGARI KOTO GADANG KABUPATEN DHARMASRAYA - Rizka Fatiha Rahmi; Mansyur, Herlinda (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2025)
Abstract This research aims to uncover and describe the existence of the Kuda Lumping dance of the Turonggo Mudo group in Nagari Koto Gadang, Dharmasraya Regency. This type of research is qualitative with a descriptive analytical method. The research instruments include the researcher themselves, assisted by writing tools and a camera. Data was collected through literature study, observation, interviews, and documentation. The steps for analysing the data are data collection, data reduction, data description, and drawing conclusions. Research results show that the existence of Kuda Lumping dance of the Paguyuban Turonggo Mudo in Nagari Koto Gadang Dharmasraya is still developing and alive within the community life of Nagari Koto Gadang. Until now, Kuda Lumping dance is still performed regularly, especially during the annual celebration of Indonesia's Independence Day. This indicates that the art form not only has a place within the Javanese community but is also accepted and enjoyed by the Minang community as part of local cultural diversity. The Kuda Lumping art in the area serves various functions, including as a means of entertainment, a medium for symbolic communication, an economic driver, and a part of ritual activities. Thus, Kuda Lumping has become an integral part of the socio-cultural life of the Nagari Koto Gadang community.